Promotional and social media strategy for budget hotel: the case at Maxim Hotel, Kota Kinabalu / Siti Hajar Khazali and Rozilydia Jaafar - Khazali, Siti Hajar; Jaafar, Rozilydia (2017)
Tourism is one of the important income-generating sectors in Sabah and contributes to its high economic growth. The objective of this study is to analyze the current business situation of Maxim Hotel, to recommend appropriate promotional strategies (social media marketing) and to recommend new and alternative strategies for Maxim Hotel. The unit of analysis is the stakeholder of the hotel, which comprised the management team, guests of the hotel, people around the business area, and the competitors. This study distributed the questionnaire to 30 respondents. The research method employed in this study is an interview with the owner of Maxim Hotel, distributed questionnaire to the people around the business area and competitors, and the' analysis of SWOT and TOWS. The findings of the interviews and observation revealed that Maxim Hotel did not focus on the promotional strategies. The development of an official website and the setting up of its Facebook and Instagram accounts were a significant contribution of this study towards the promotional effort of Maxim Hotel.